Modulation of spontaneous alpha brain rhythms using low-intensity transcranial direct-current stimulation - Spitoni, Grazia F.; Di Russo, Francesco; Cimmino, Rocco Luca; Bozzacchi, Chiara; Pizzamiglio, Luigi (Frontiers in Human Neuroscience, 2013)
Transcranial direct-current stimulation (tDCS) is a form of neurostimulation in which a constant, low current is delivered directly to the brain area of interest by small electrodes. The overall aim of this study was to examine and monitor the modulation of brain activity by electroencephalogram (EEG) in the frequency domain during tDCS in the resting state. To this end, we considered the modulation of spontaneous EEG to be a marker of the perturbation that was induced through the direct current (1.5 mA for 15 minutes). In all conditions (anodal, cathodal, and sham), an active electrode was placed over the right posterior parietal cortex, and a reference electrode was placed on the ipsilateral deltoid muscle. The EEG was recorded using a 64-channel system. The effect of tDCS was limited to the alpha rhythm, and the anodal stimulation significantly affected the alpha rhythm, whereas the cathodal stimulation did not elicit any modifications. Further, we observed modulation of alpha activity in areas that were stimulated directly through tDCS and in anterior noncontiguous areas. Finally, the anodal effect peaked 7.5 minutes after stimulation and decreased gradually over time. Our study demonstrates that in the resting brain, monocephalic anodal tDCS over posterior parietal areas alters ongoing brain activity, specifically in the alpha band rhythm. Our data can be used to fine-tune tDCS protocols in neurorehabilitation settings.